PENGARUH LABA KOTOR DAN LABA BERSIH DALAM MEPREDIKSI ARUS KAS MASA MENDATANG PADA PERUSAHAAN MANUFAKTUR DAN PERUSAHAAN JASA YANG TERDAPAT DI BURSA EFEK INDONESIA (BEI) - Susi Marni; Surya Tegar Widjiantoro (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This study aims to determine the effect of gross profit and net income in predicting future cash flows in manufacturing companies and service companies in 2017-2019.The population in this study there are 169 companies incorporated from the manufacturing sector and service sector with a random sample obtained 21 companies. The final result of this research is: first, gross profit (X1) have an effect not significant to predict aru kas (Y) future. Second, net income (X2) has a significant effect on future cash flows (Y). And the third, simultaneous gross profit and net profit gives 91.9% influence to future cash flows while the rest of 8.1% is influenced by other factors outside these two variables